Palaeoenvironmental data indicate late quaternary anthropogenic impacts on vegetation and landscapes in Mzimba, northern Malawi - Wright, David K.; Ivory, Sarah J.; Birk, Jago J.; Choi, Jeong-Heon; Davies, Benjamin; Fiedler, Sabine; Davis, Jacob; Kaliba, Potiphar; Thompson, Jessica C. (Frontiers in Environmental Archaeology, 2024)
Landscapes are formed by long-term interactions between the underlying geology and climatic, edaphic and biotic factors, including human activity. The Kasitu Valley in the Mzimba District of northern Malawi includes the Kasitu River and its adjacent floodplains and uplands, and it has been a location of sustained human occupation since at least 16 thousand years ago (ka) based on archaeological excavations from rockshelters. We trace the changing ecology and geomorphology of the region through soil stable isotopes (δ 13 C, δ 15 N), microcharcoal and fossil pollen analysed from alluvial terraces dated by Optically Stimulated Luminescence, and wetland auger cores and archaeological sites dated by radiocarbon. Our results suggest that the region was primarily covered in mosaic forest at ca. 22.5 ka. Middle and Late Holocene samples (6.0-0.5 ka) show an increasingly open, herbaceous landscape over time with an inflection toward more abundant C4 vegetation after 2 ka. Significant upland erosion and terrace formation is also evidenced since 2 ka alongside high concentrations of microcharcoal, suggesting more intensive use of fire. Faecal biomarkers simultaneously indicate higher numbers of humans living adjacent to the archaeological site of Hora 1, which may be indicative of an overall population increase associated with the arrival of Iron Age agropastoralists. More recently, the introduction of exogenous commercial taxa such as Pinus sp. are correlated with regional afforestation in our proxy record. These results show increasing stepwise human impacts on the local environment, with deforestation and maintenance of open landscapes correlated with the regional introduction and intensification of agriculture during the Late Holocene.